ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN DI PT SARI WARNA ASLI UNIT 1 KEBAKKRAMAT KARANGANYAR - Gostaf Vio Girrad Wiratama; Edi Purwanto; Dian Noor Citra Perdana (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to determine the effect of Work Discipline (X1), Work Environment (X2), and Leadership (X3) on Employee Performance (Y) at PT Sari Warna Asli Unit 1 Kebakkramat, Karanganyar. This research employs a quantitative approach utilizing multiple linear regression analysis processed through the SPSS 25 program. Primary data were gathered via questionnaires from a sample size of 92 employees of PT Sari Warna Asli. The multiple linear regression equation obtained from the analysis is Y = -0.346 + 0.189X1 + 0.373X2 + 0.537X3. The partial t-test results indicate that: (1) Work Discipline (X1) has a positive and significant effect on Employee Performance, with tcount (2.776) > ttable (1.987).(2) Work Environment (X2) has a positive and significant effect on Employee Performance, with tcount (4.012) > ttable (1.987)$. (3) Leadership (X3) has a positive and significant effect on Employee Performance, with tcount (7.685) > ttable (1.982).(3) Among the three independent variables, Leadership (X3) is identified as the most dominant factor influencing Employee Performance. Furthermore, the F-test results demonstrate a simultaneous significant effect, where Fcount (201.801) > Ftable (3.098), meaning that Work Discipline, Work Environment, and Leadership collectively influence Employee Performance. The Coefficient of Determination (R2) yields a value of 0.934 or 93.4%, proving that the independent variables robustly contribute to Employee Performance at PT Sari Warna Asli Unit 1 Kebakkramat, Karanganyar. The remaining 6.6% is influenced by other variables outside the scope of this study Keywords: : Work Discipline, Work Environment, Leadership, Employee Performance.